2018
DOI: 10.1080/13621718.2018.1443997
|View full text |Cite
|
Sign up to set email alerts
|

Improving austenitic stainless steel resistance spot weld quality using external magnetic field

Abstract: A ring-shaped permanent magnet is applied in resistance spot welding to improve the weld quality of austenitic stainless steel. Under the action of an external magnetic field, the profile of the weld nugget became peanut-shaped instead of ellipsoidal. The crystal orientation near the faying surface was less directional, and equiaxed grains were formed in weld nugget centre. Moreover, the shrinkage cavities tendency in traditional resistance spot welds was reduced. The relatively slow cooling speed could cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…23 reported that solidification cracks in weld zone due to the solidification done in austenitic mode and it can be prevented by the presence of delta ferrite. 24…”
Section: Resultsmentioning
confidence: 99%
“…23 reported that solidification cracks in weld zone due to the solidification done in austenitic mode and it can be prevented by the presence of delta ferrite. 24…”
Section: Resultsmentioning
confidence: 99%
“…Literatürde harici manyetik alan kaynağı olarak mıknatıs kullanılan çoğu uygulama çalışmasında (Li ve ark. 2011, 2018…”
Section: Tartışma Ve Sonuçunclassified
“…To improve the weld quality in a energy-efficient method, magnetically assisted resistance spot welding (MA-RSW) technology was proposed by Shen et al (2011). Experimental studies on dual-phase steel (Qi et al, 2020), stainless steel (Li et al, 2018), aluminum CONTACT Yongbing Li yongbinglee@sjtu.edu.cn alloy (Huang et al, 2020), magnesium alloy (Yao et al, 2014) and Al/Ti dissimilar materials (Li et al, 2015) have shown that an external magnetic field (EMF) can enlarge the nugget size, reduce the shrinkage defects, and improve the mechanical performance of weld joints. However, these studies were based on experimental methods, and the control mechanism of an EMF on the flow behaviors of molten metal cannot be observed because the weld formation process is completely invisible, which limits further improvement of the weld performance.…”
Section: Introductionmentioning
confidence: 99%